The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.18061/emr.v15i1-2.6863
|View full text |Cite
|
Sign up to set email alerts
|

Singing and Accompaniment Support the Processing of Song Lyrics and Change the Lyrics' Meaning

Abstract: A growing body of evidence indicates that music can support the processing of language. Some of its beneficial effects may even occur after one exposure. Accompaniment can also have an impact: in a-cappella singing, silences and out-of-key notes may confuse listeners, while accompaniment avoids silences and elucidates both rhythm and harmony, thereby supporting music-processing and concentration. These hypotheses were tested in two experiments. In a classroom setting, 271 pupils (M = 15.7 years old, SD = 0.9),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 59 publications
1
6
0
Order By: Relevance
“…Additionally, the exclusion of items evaluating the quality of the lyrics has weakened the model, as fewer factors are significant right now. Yet, the results support the assumption that the differences in the results for the two studies, observed in Schotanus (2020a), are due to different ratings.…”
Section: Factor Analysessupporting
confidence: 70%
See 3 more Smart Citations
“…Additionally, the exclusion of items evaluating the quality of the lyrics has weakened the model, as fewer factors are significant right now. Yet, the results support the assumption that the differences in the results for the two studies, observed in Schotanus (2020a), are due to different ratings.…”
Section: Factor Analysessupporting
confidence: 70%
“…After each track they filled out a questionnaire, mainly consisting of Likert-scale items, seven of which were asked for music and lyrics separately. For more details concerning participants, materials and procedure, see Schotanus (2020a), and for songs (lead sheets and recordings) and questionnaires, see Schotanus (2017).…”
Section: Methods Participants Materials and Proceduresmentioning
confidence: 99%
See 2 more Smart Citations
“…One example of these “affects” is sincerity (which has been mentioned by Pattison [2015]). Other interactive emotional communication through music may involve a nagging or a calming quality, which is defined by the effect on the listener (Schotanus, 2020a, 2020b, Part 3), and social or psychological constructions (Warrenburg, 2020) such as the impression of authenticity, which is very important in the music industry (Auslander, 1999; Frith, 1981/2007). Authenticity and sincerity may not seem to be directly related to emotion, yet, if a singer is interpreted to be inauthentic or insincere, this will affect both the listener’s interpretation of the emotional state of the singer and the listener’s own emotional state, and consequently it will also affect the listener’s ability to connect with the music.…”
mentioning
confidence: 99%